Web camera-enabled material research: an acoustooptic example - Alexieva, G.; Traykov, I.; Strashilov, V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
The applicability of standard PC web cameras to material testing has been discussed. A simple method for measuring the acoustic velocity and attenuation of transparent solid materials has been described as an illustrative example. It is based on the acoustooptic diffraction in the Raman–Nath limit and a digital readout and processing of the information obtained. Acceptable accuracy of the results is achieved. The method is particularly suitable for very quick testing of high loss materials.
Optica Applicata, Vol. 37, 2007, nr 3, s. 313-322
Keywords: optyka; web camera; acoustooptic diffraction; material testing; acoustic velocity and attenuation